2019 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--32170
|View full text |Cite
|
Sign up to set email alerts
|

Board 102: Exploring Professional Identity Formation in Undergraduate Civil Engineering Students Who Experience Disabilities: Establishing Definitions of Self

Abstract: is a post-doctoral researcher in the Department of Engineering Education at Virginia Tech. Her primary research interests include professional identity formation in undergraduate civil engineering students, grounded theory methods, and theory development. Her current work includes the exploration of professional identity formation in civil engineering students who experience disabilities and the ways in which this identity is influenced by students' academic relationships, events, and experiences. Dr. McCall h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…However, grounded theory in engineering education is beginning to move beyond the application of methods to generate non-theory and toward the implementation of a methodology to develop theory. Groen-McCall and colleagues (Groen, 2017;Groen et al, 2017Groen et al, , 2018Groen-McCall et al, 2019), Faber and colleagues (Faber et al, 2019), and Simmons and colleagues (Simmons, 2012;Simmons & Martin, 2014) have utilized constructivist grounded theory to explore processes of professional and researcher identity formation in undergraduate engineering students and student perceptions of family roles in academic decision making. In these studies, constructivist grounded theory methodology served as a flexible guideline for contextualized theory generation that was loosely structured by sensitizing concepts yet driven by emerging findings grounded in the data.…”
Section: Articulate Grounded Theory Implementation and Outcomesmentioning
confidence: 99%
“…However, grounded theory in engineering education is beginning to move beyond the application of methods to generate non-theory and toward the implementation of a methodology to develop theory. Groen-McCall and colleagues (Groen, 2017;Groen et al, 2017Groen et al, , 2018Groen-McCall et al, 2019), Faber and colleagues (Faber et al, 2019), and Simmons and colleagues (Simmons, 2012;Simmons & Martin, 2014) have utilized constructivist grounded theory to explore processes of professional and researcher identity formation in undergraduate engineering students and student perceptions of family roles in academic decision making. In these studies, constructivist grounded theory methodology served as a flexible guideline for contextualized theory generation that was loosely structured by sensitizing concepts yet driven by emerging findings grounded in the data.…”
Section: Articulate Grounded Theory Implementation and Outcomesmentioning
confidence: 99%
“…In this paper, mental health challenges and disabilities are both discussed, sometimes interchangeably, due to the ways in which interviewees themselves responded to questions. Because of these conflations, the data provides insights into where and how overlaps between the two phenomena occur, and adds to previous findings that mental health is often worse for engineering students who also identify as having a disability [3], [12]. For example, in our data, interviewees explain how anxiety (a mental health challenge) caused them to need different testing formats and spaces (which qualifies for a disability accommodation from disability service centers).…”
Section: Introductionmentioning
confidence: 49%
“…Prior work has identified that college students with non-apparent disabilities are more likely to drop-out of school and academically underperform than their peers without non-apparent disabilities [11]. In part, this likelihood stems from the fact that for many students with non-apparent disabilities, disclosure often includes an assessment process in which a student considers the stability of their nonapparent disability, implications for not receiving an accommodation, and the stigma that may be attached to them in light of their disclosure [11], [13].…”
Section: The Significance Of Non-apparent Disabilities and Identitymentioning
confidence: 99%
“…Such factors include the underrepresentation of disabled individuals within research and industry [1]; systemic and personal barriers [2], [3], and sociocultural expectations within and beyond engineering education-related contexts [4]. These findings provide a foundational understanding of the external and environmental influences that can shape how students with disabilities experience higher education, develop a sense of belonging, and ultimately form professional identities as engineers [4]- [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation